2010
DOI: 10.1179/147683010x12611460763968
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary excretion of a 3-(3-hydroxyphenyl)-3-hydroxypropionic acid (HPHPA), an abnormal phenylalanine metabolite ofClostridiaspp. in the gastrointestinal tract, in urine samples from patients with autism and schizophrenia

Abstract: A compound identified as 3-(3-hydroxyphenyl)-3-hydroxypropionic acid (HPHPA) was found in higher concentrations in urine samples of children with autism compared to age and sex appropriate controls and in an adult with recurrent diarrhea due to Clostridium difficile infections. The highest value measured in urine samples was 7500 mmol/mol creatinine, a value 300 times the median normal adult value, in a patient with acute schizophrenia during an acute psychotic episode. The psychosis remitted after treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 35 publications
2
94
1
1
Order By: Relevance
“…The tumor promoting activities of p -cresol and related compounds have been known for decades (Boutwell et al 1959). In addition to p -cresol, we observed 3-(3-hydroxyphenyl)-3-hydroxypropionate, a metabolite that has been associated with members of Clostridiae (Shaw 2010), to be elevated in colon cancer patients’ urine compared to rectal cancer patients’ urine. Moreover, urinary butyrate levels were increased in late-stage CRC patients prior to surgery.…”
Section: Discussionmentioning
confidence: 91%
“…The tumor promoting activities of p -cresol and related compounds have been known for decades (Boutwell et al 1959). In addition to p -cresol, we observed 3-(3-hydroxyphenyl)-3-hydroxypropionate, a metabolite that has been associated with members of Clostridiae (Shaw 2010), to be elevated in colon cancer patients’ urine compared to rectal cancer patients’ urine. Moreover, urinary butyrate levels were increased in late-stage CRC patients prior to surgery.…”
Section: Discussionmentioning
confidence: 91%
“…8) [157]. 3 -Hydroxy-phenylhydracrylic acid has been identified as a phenylalanine catabolite of incompletely characterised metronidazole-sensitive bacteria [162], and proposed as a urinary biomarker for a range of neurological, gastrointestinal, and psychiatric disorders [163], and 4 -hydroxyphenylhydracrylic acid has been observed in patients with gastro-intestinal disease [164]. The definitive answer to the origin and significance of phenylhydracrylic acids is still lacking, but it has been shown that some Bacillus spp.…”
Section: Controls Used In Model Fermentations Have Clearly Demonstratmentioning
confidence: 99%
“…It was proposed that these metabolites were produced by the gut bacteria. High concentrations of an abnormal phenylalanine metabolite have been found in the urine of people with autism and schizophrenia, up to 300x normal adult values, which is likely due to multiple species of anaerobic bacteria in the Clostridium genus [73]. Others have detected abnormally high concentrations of hippurate in the urine in association with autism [74].…”
Section: Gut Dysbiosis Autism and Colitismentioning
confidence: 99%